PERAN DINAS KEPEMUDAAN, OLAHRAGA DAN PARIWISATA KABUPATEN INDRAGIRI HULU DALAM PENGEMBANGAN WISATA DANAU MEDUYAN DI DESA KOTA LAMA TAHUN 2022-2024 - Nisa, Larasita Iffatun; Pane, Rico Purnawandi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This This research is motivated by the potential of Lake Meduyan Tourism in Kota Lama Village, Indragiri Hulu Regency, which has not been optimally developed despite being designated as a priority destination in the RIPPARDA. The main problems include fluctuations in visitor numbers, limited facilities, suboptimal promotion, and suboptimal destination management. This study aims to describe the role of the Indragiri Hulu Regency Youth, Sports, and Tourism Office in the development of Lake Meduyan Tourism in 2022–2024, based on Ryaas Rasyid's theory of government roles encompassing regulator, dynamicator, and facilitator functions. This study uses a qualitative descriptive approach. Data were collected through purposive sampling interviews and documentation involving the office, tourism awareness groups (Pokdarwis), and visitors. The results show that as a regulator, the government has established RIPPARDA and designated Lake Meduyan as a priority destination but lacks SOPs, visitor regulations, and a security system. As a dynamicator, the government has encouraged community participation through mutual cooperation activities and tourism events, but private sector partnerships have not materialized. As a facilitator, the government has enhanced community capacity through training programs, but the provision and maintenance of physical facilities remain limited. Keywords: Government Role, Tourism Development, Regulator, Dynamizer, Facilitator